DOZ047.17: Characterization of esophageal motility in children with operated esophageal atresia using high-resolution impedance manometry and pressure flow analysis. (24th June 2019) - Courbette, O; Omari, T; Aspirot, A; Faure, C
Abstract: Background: Esophageal dysmotility is common in patients with esophageal atresia (EA). High-resolution impedance manometry (HRIM) and pressure flow analysis (PFA) allow characterization of biomechanical bolus flow and swallow properties. The aim of this study was to characterize esophageal motility and bolus flow propulsion in children who underwent surgical EA repair. Patients and Methods: HRIM was used in 14 children with EA (type C, n  = 13; type A, n  = 1). Study was performed at a median (range) age of 11 years (5–17). The HRIM recordings were analyzed using conventional esophageal pressure topography and PFA (AIMplot software deployed via the open access Swallow Gateway application) and were compared with 13 patient controls (median age 14 years, range 5.75–17; P  = NS vs patients) who underwent HRIM considered as normal according to Chicago classification and for whom the manometry results did not lead to treatment changes. Medical charts were reviewed for medical/surgical history and symptoms were assessed by standardized questionnaires. Results: Esophageal peristaltic motor patterns were abnormal in all EA patients and were subdivided in two groups: Group A with presence of distal contraction in ≥ 50% of the swallows ( n  = 6) and Group B with presence of distal contractions in < 50% of the swallows ( n  = 8). IRP4s was similar in EA and controls. Bolus transport was impaired as shown by the higher impedance ratio (IR) in EA than in controls (0.47 vs 0.22, P  < 0.001). In Group A, proximal and distal contractile integrals were lower than in controls ( P  < 0.001) and distal contractile velocity was shorter in EA ( P  < 0.01). IR was lower in Group A than in Group B ( P  < 0.01). In this sample, symptoms of dysphagia and presence of gastric metaplasia or esophagitis were not correlated with any of the measures determined. Conclusions: Bolus transport as measured by impedance ratio is severely altered in EA patients but is not predictive of symptoms. The presence of residual distal contractions is associated with a more efficient bolus propulsion. Whether this is associated with a better outcome warrants further studies.